Comparison of the Effects of Acceptance and Commitment Therapy and Emotion-Focused Therapy on Mental Vitality in Caregivers of Elderly Parents - Zahra Noorali; Reza Khakpour; Pante'a Jahangir (Elderly Health Journal, 2024)
Introduction: Caregiving burden for older adults can impose significant physical and emotional demands, leading to a reduction in mental vitality among caregiver children. Effective psychological interventions are crucial to enhance their well-being. Methods: This quasi-experimental study included two psychological interventions: Acceptance and Commitment Therapy (ACT) and Emotion-Focused Therapy (EFT), with baseline, post-test, and follow-up phases, along with a control group for comparison. The research population comprised female caregivers who accompanied their older adults to health centers in Tehran. From a total of 169 individuals, 45 participants were selected through convenience sampling and were randomly assigned to three groups of 15 participants each, forming two experimental groups and one control group. Data were collected using the Ryan and Frederick Mental Vitality Questionnaire, and multivariate covariance analysis was applied for data analysis to assess the effectiveness of the interventions. Results: The analysis showed that both ACT and EFT interventions significantly improved the mental vitality of caregiver children in the post-test and follow-up stages compared to the control group (p = 0.001). Additionally, EFT demonstrated a greater impact on enhancing mental vitality compared to ACT. Conclusion: Emotion-focused interventions, such as EFT, can be considered a more effective approach for improving the mental vitality of caregiver children of older adults. This highlights the importance of incorporating tailored emotional support strategies in caregiver assistance programs.